Pengaplikasian 5S dan Kaizen Sebagai Upaya Peningkatan Kualitas Produksi Area Spot Welding di Perusahaan Manufaktur Otomotif - Muhamad Tegar Maulana; Dwi Ayu Puspita Sari; Like Andreas Kindangen; Yusuf Eka Setiawan; Yudi Prastyo (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Improving production quality is one of the key factors in maintaining a company’s competitiveness, particularly in the manufacturing sector such as automotive and electronics. One approach that can be applied to achieve this efficiency is the 5R/5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) and Kaizen, which focus on establishing an orderly, clean, and disciplined work culture as practiced in Japanese industries. This study aims to analyze the implementation of the 5S and Kaizen methods as an effort to improve the quality of the spot welding production process at PT.Manufacture Automotive. The research was carried out through field observations as an application of industrial theory in a real work environment. The methods used include direct observation, interviews, analysis of 5S implementation, and evaluation of conditions before and after improvements. Data were collected using a checklist audit sheet and analyzed descriptively to measure changes in efficiency and workplace organization. The results show that the implementation of the 5R/5S method successfully improved work quality and productivity. The 5S- condition assessment score increased from 22.24% (Not good category) to 67% (fair category) after the improvements were implemented.